An Overview on McCune-Albright Syndrome: Secondary Amenorrhea in a Case of Early Puberty without Gonadotropin - Subbiah, Sridhar; Nazirudeen, Roshan; Natarajan, Sundari; Natarajan, Vasanthiy; Jayaraman, Sangumani (New Advances in Medicine and Medical Science Vol. 6, 2023)
The present case highlights the fact that careful examination for syndromic features and periodic follow up are important in all cases of precocious puberty. Precocious puberty is the appearance of secondary sexual characteristics before the normal limit of age of onset of puberty for the race and sex of the individual. It may be gonadotropin dependent or gonadotropin independent. A rare condition known as McCune-Albright syndrome (MAS) is characterised by the triad of café-au-lait macules, polyostotic fibrous dysplasia of bone, and early puberty. Here, we describe a case of childhood onset gonadotropin independent precocious puberty who presented at 19 years of age with secondary amenorrhea. Based on the clinical features and investigations, patient diagnosed to have MAS. She was given zoledronic acid infusion for fibrous dysplasia. Amenorrhea was treated with medroxyprogesterone 10 mg daily for 14 days, followed by low dose combined oral contraceptive therapy, following which menstrual cycles resumed. Typically, the lesions of fibrous dysplasia are most active during childhood and adolescence, tending to become quiescent in adult life, new active lesions being rare in adults. Bilateral encroachment of the optic foramina was present along with multiple active polyostotic lesions, which is unusual at this age even though the fibrous dysplasia was asymptomatic at presentation.